Relationship Between Respondent Characteristics With Implementation Of Public Infection Prevention By Midwife In UPTD Puskesmas Mompang District Panyabungan District Mandiling In 2021 - Lidya Natalia Br Sinuhaji (Science Midwifery, 2021)
Puerperal infection is an infection - inflammation of all genital organs during the puerperium for any reason provided that the body temperature rises above 38ºC without counting the first day and consecutively for 2 days. One of the causes of puerperal infections is manipulation by helpers: too often do internal examinations, the tools used are not pure for pests. The aim of this study was to determine the relationship between the characteristics of the respondents and the implementation of prevention of puerperal infections by private practicing midwives at the Mompang Health Center, Panyabungan District, Mandailing Regency, Tahun 2021. This type of research is descriptive-correlative with a cross-sectional approach. This research was conducted from February to May 2021. Researchers used a total sampling technique. Data analysis used chi – square. Based on the results of the study, the majority of 40 respondents aged between 22-39 years were 23 people (57.5%), D - I Midwifery education were 22 people (55%), work experience 14-26 years were 27 people (67.5 %), and less knowledgeable as many as 24 people (60%). From the results of data analysis on the relationship between age and the implementation of prevention of puerperal infections, it was found that the value of p = 0.002 and OR = 11.40 means that there is a significant relationship. Education with the implementation of puerperal infection prevention obtained p = 0.032 and OR = 5.343 meaning that there was a significant relationship and work experience with the implementation of puerperal infection prevention obtained p = 0.063 and OR = 5.923 meaning that there was no significant relationship. From the results of this study it is hoped that midwives as health workers will further improve their experience, knowledge, quality of service in preventing puerperal infections